Analysis of shunting locomotive operating modes when performing traction tasks (Transport systems and technologies, 2023)
The paper considers the modes of operation of shunting diesel locomotives ČME3 when performing traction tasks at the service areas of the locomotive depot Koziatyn. A mathematical model of train movement with a ČME3 diesel locomotive has been developed, which has been used to solve a series of traction problems. It was found that the operating modes of a diesel engine are most influenced by the profile of the track section. It is determined that when moving from the Koziatyn station, the relative duration of the traction mode is 14...39% of the total movement time. When moving in the direction of the Koziatyn station, the relative duration of the traction mode is 28...90%. In the traction mode, the diesel engine operates at rated power. For the examined sections of the movement, we evaluated the diesel fuel consumption for a serial diesel locomotive, a diesel locomotive with a modern diesel engine, and a battery locomotive charged from an onboard diesel generator set. It has been determined that a diesel locomotive with a modern diesel engine consumes 18...22% less fuel than a standard diesel locomotive. In the case of a battery locomotive, fuel consumption can be either lower or higher compared to a diesel locomotive with a modern diesel engine. At the same time, the accumulation of energy in the onboard energy storage device during electrodynamic braking and its use in traction modes helps to reduce fuel consumption.
Keywords: shunting locomotive, modernization, energy efficiency, energy storage, traction task